Serum concentrations of S100-A11 and AIF-1 are elevated in cervical cancer patients with lymph node involvement - Maděrka, Martin; Dvořák, Vladimír; Hambálek, Jozef; Stejskal, David; Krejčí; Švesták, Marek; Langová, Kateřina; Pilka, Radovan (Ceska gynekologie, 2021)
OBJECTIVE: The aim of this study was to compare the serum levels of TFF3, AIF-1, S100-A11 and DKK1 in surgically staged patients with cervical cancer, and in healthy female controls. METHODS: In total 85 consecutive patients dia-gnosed at the Department of Obstetrics and Gynecology, University Hospital in Olomouc with cervical cancer undergoing radical hysterectomy or fertility sparing surgery with pelvic lymphadenectomy were included. Ninety patients who underwent elective total hysterectomy for nonmalignant disorder represented a control group. In all patients, preoperative serum samples were taken and separated; the sera were all stored at -80 °C until analysis for TFF3, AIF-1, S100-A11 and DKK1. RESULTS: According to the final histopathological examination, 32 (40.5%) out of 79 cervical cancer patients with microscopically examined lymph nodes were lymph node-positive. S100–A11 (P < 0.0001) and AIF-1 levels (P < 0.0001) were higher in cervical cancer patients than in controls. Furthermore, the serum levels of S100–A11 (P > 0.04) and AIF-1 (P > 0.01) were significantly higher in lymph node-positive patients as compared to lymph node-negative patients. The levels of TFF3 and DKK1 were higher (P < 0.0001) in controls than in cervical cancer patients and were not different in groups with or without nodal involvement.. CONCLUSION: S100-A11 and AIF-1 represent potential bio-markers in patients with cervical cancer. Moreover, the levels of S100-A11 and AIF-1 increase in patients with lymph node involvement.
Keywords: hysterektomie; Neoplasm Staging; cervical cancer; Retrospective Studies; lidé; oncogynecology; Lymphatic Metastasis; Humans; Uterine Cervical Neoplasms; retrospektivní studie; nádory děložního čípku; DKK1; lymfatické uzliny; biomarkers; TFF-3; Lymph Nodes; S100–A11; Hysterectomy; biomarkers; lymfatické metastázy; AIF-1; staging nádorů; lymfadenektomie; TFF3; ženské pohlaví; Female; Lymph Node Excision